The Sustainability of Skipjack in Sikka Regency: An Analysis of Economic Dimension - Natalia Yessica Onya Parera; Barnabas Pablo Puente Wini Bhokaleba; Tomi Ramadona (Berkala Perikanan Terubuk, 2021)
Skipjack has an essential economic value and it is spread in almost Indonesia’s territorial waters. Skipjack resource utilization activities have contributed greatly to the fisheries sector in Indonesia. The need and high market demand for skipjack causes the fishing intensity is increase. The increasing of skipjack fishing intensity by fishermen in pemana village is concerned that it will threaten the preservation and sustainability of the utilization skipjack resources. The Pemana village is the biggest skipjack producer in Sikka regency. The increasing of the skipjack fishing intensity in this area also occurs every year. Therefore, it is need a skipjack fisheries management in order to ensure the sustainability of skipjack fisheries. A management is development such as ecologically, socially and economically sustainable. This study was aimed to find out the status of sustainable skipjack fisheries that investigated from the economic dimension. The analysis which used was Rapfish (Rapid Apparaisal for Fisheries). The result of Multi-Dimensional Scaling (MDS) revealed that sustainability status of the economic dimension of the skipjack fisheries in Sikka regency was 53,108 or it was in a fair sustainable status. The result of sensitivity Analysis/Leverage of Attributes revealed that there were two key factors of the sustainability of skipjack fisheries such as other income and market oriented. The result of Monte Carlo analysis (eror effect/error) revealed that this analysis had a high confidence level and could be used as an instrument in economic dimension evaluation of skipjack fisheries resources.